2006
DOI: 10.1093/europace/eul035
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of the signal-averaged ECG in arrhythmogenic right ventricular cardiomyopathy: correlation with arrhythmic events and echocardiographic findings

Abstract: We detected a progressive increase in delayed ventricular conduction by SAECG not associated with significant echocardiographic changes. Therefore, the conduction disturbance seems to increase independently from anatomical alterations. The baseline SAECG and echocardiographic parameters, more than their modifications during follow-up, appear to be useful in identifying patients with sustained VT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 21 publications
1
23
1
6
Order By: Relevance
“…Although there is controversy regarding the optimal filter to be used, bidirectional 25 to 250 Hz or 40 to 250 Hz filters are used most frequently (Breithardt et al, 1991). Some studies in humans, however, also use the 80 to 250 Hz filter and often compare the SAECG results obtained with these three types of filters (Turrini et al, 1999;Folino et al, 2006;Steriotis et al, 2009). In dogs, most SAECG studies are performed using only the 40 to 250 Hz filter (Kushner et al, 1996;Calvert et al, 1998a;Calvert et al, 1998b;Ferreira, Camacho, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is controversy regarding the optimal filter to be used, bidirectional 25 to 250 Hz or 40 to 250 Hz filters are used most frequently (Breithardt et al, 1991). Some studies in humans, however, also use the 80 to 250 Hz filter and often compare the SAECG results obtained with these three types of filters (Turrini et al, 1999;Folino et al, 2006;Steriotis et al, 2009). In dogs, most SAECG studies are performed using only the 40 to 250 Hz filter (Kushner et al, 1996;Calvert et al, 1998a;Calvert et al, 1998b;Ferreira, Camacho, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This susceptibility is particularly seen in dogs suffering from ARVC, a hereditary autosomal dominant disease characterized by slow cardiac conduction through the myocardium infiltrated by fibrous tissue, causing onset of fatal ventricular arrhythmias and sudden death (Folino et al, 2006;Spier et al, 2001;Harpster , 1991;Meurs et al, 1999;Meurs, 2004;Basso et al, 2004). Such slow conduction of cardiac electrical stimulation can result in the appearance of a greater number of high-frequency and lowvoltage signals in the SAECG, which are suggestive of LP; however, such signals were not found in the SAECG of Boxer dogs compared to German Shepherds in this study.…”
Section: Discussionmentioning
confidence: 99%
“…LVPs were observed in more than 50% of patients with ARVC, and are minor diagnostic criteria in this setting (Santangeli et al, 2008). SAECG has shown particular reliability in ARVC, considering the classical location of the myocardial alterations in the right ventricle, which induce a delayed potential only in the terminal portion of QRS (Folino et al, 2006). Folino et al (Folino et al, 2006) detected a progressive increase in delayed ventricular conduction, not associated with significant echocardiographic changes in patients with ARVC, and concluded that the baseline SAECG and echocardiographic parameters are useful in identifying patients with sustained VT.…”
Section: Cardiomyopathiesmentioning
confidence: 98%
“…Arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC) i s a n i n h e r i t e d myocardial disease, characterized by fibro-fatty substitution of the right ventricle (Corrado & Thiene, 2006). The fibro-fatty areas can create reentry circuits, the substrate for repetitive ventricular arrhythmias and a delayed, fragmented activation font (Folino et al, 2006). The typical clinical manifestations are ventricular arrhythmias with left BBB pattern.…”
Section: Cardiomyopathiesmentioning
confidence: 99%
See 1 more Smart Citation